Aplicação pré-colheita de ácido giberélico no metabolismo antioxidante em pedúnculos de clones de cajueiro-anão - Xavier, Cicera Vanuza Viana (2017)
The cashew tree (Anacardium occidentale L.) stands out among the native fruit species in northeastern Brazil by both the enormous potential as table fruit, as in industrial processing. The Consumption in natura is growing considerably every season due to the high interest of the population in health promotion, linked to foods rich in antioxidant. Among the agricultural management practices, the use of plant growth regulators can be an alternative in promoting the improvement of the functional quality of cashew apples. This study aimed to evaluate the effects of GA3 pre-harvest application in different doses (0, 60, 120 and 180 mg L-1), on the postharvest quality of two clones of dwarf cashew (CCP 76 and BRS 189) specifically on the metabolism of bioactive compounds and antioxidant enzymes. The cashew apples, coming from Campus Pacajus-CE Experimental belonging to Embrapa were treated with GA3 two days before harvest at mature stage. The evaluations showed that pre-harvest application of GA3 significantly influenced the phenylalanine ammonia lyase (PAL ) activity and superoxide dismutase (SOD) in both clones, but it did not affect the activity of catalase (CAT), nor the content of phenolics and carotenoids, and total antioxidant activity. The GA3 reduced the activity of PAL enzyme in CCP 76 clone, but promoted an increase in the activity of this enzyme in BRS 189 clone. These cashew clones, total antioxidant activity was correlated to the content of carotenoids. The BRS 189 clone cashew introduced himself as best source of antioxidants due to higher content of trans-cinnamoyl and SOD activity.